Anatomical and Neurochemical Correlates of Parental Verbal Abuse: A Combined MRS—Diffusion MRI Study - Kim, Dohyun; Yoo, Jae Hyun; Park, Young Woo; Kim, Minchul; Shin, Dong Woo; Jeong, Bumseok (Frontiers in Human Neuroscience, 2019)
Despite the critical impact of parental dialogue on children who remain physically and psychologically dependent, most studies have focused on brain alterations in people exposed to moderate-to-high levels of emotional maltreatment with/without psychopathology. We measured metabolites in the pregenual anterior cingulate cortex (pgACC) acquired with single-voxel proton magnetic resonance spectroscopy and anatomical connectivity assessed with probabilistic tractography in 46 healthy young adults who experienced no-to-low level parental verbal abuse (paVA) during their childhood and adolescence. The partial least square regression (PLSR) model showed that individual variance of perceived paVA was associated with chemical properties and structural connectivity of pgACC (prediction R2 = 0.23). The jackknife test was used to identify features that significantly contributed to the PLSR model; a negative association of paVA was found with myo-inositol concentration, anatomical connectivities with the right caudate and with the right transverse temporal gyrus. Of note, positive associations were also found with the left pars triangularis, left cuneus, right inferior temporal cortex, right entorhinal cortex and right amygdala. Our results showing both a negative association of frontal glial function and positive associations of anatomical connectivities in several networks associated with threat detection or visual information processing suggest both anatomical and neurochemical adaptive changes in medial frontolimbic networks to low-level paVA experiences.